Quality of Life in the Republic of North Macedonia Seen Through the Human Development Indicators - Djambaska, Elizabeta; Lozanoska, Aleksandra; Petkovski, Vladimir (IGI Global, 2020)
This chapter considers the trend of human development in the RNM, presented through the HDI. The special focus would be the links with the problem of poverty and inequality in the economy, regarding the data for the GINI, IHDI, GDI, poverty line, MPI, vulnerable employment, and youth unemployment. The research subject is the period from 2010 to 2017, using the secondary statistical data. Comparative analysis, with the countries from the CESEE countries, further improve the quality of the chapter. The RNM is a country with a high level of human development, and it is relatively equally distributed among the population. There is a difference in the distribution of the achievements of HD and an intermediate level of equality in the distribution between the genders. Income inequality expressed with the GINI index shows increase. The results confirm that there is no automatic link between the economic growth and human development. Income and gender inequality regress the quality of life in Macedonia. Growth in RNM in the past period has failed to produce the expected positive effects.